Penerapan Model Pembelajaran Role Playing terhadap Keterampilan Berbicara Peserta Didik di SMPN 1 Ampek Angkek - Azahra, Amertya; Sabri, Ahmad; Sasminelwati, Sasminelwati (ISLAMIKA, 2024)
The aim of this research is to describe: 1). Learning problems at SMPN 1 Ampek Angkek 2). Application of the Role Playing model in PAI and Character learning at SMPN 1 Ampek Angkek 3). The impact of the Role Playing model on PAI and Character learning at SMPN 1 Ampek Angkek. The method used in this research is a qualitative library research approach and interviews with teachers at SMPN 1 Ampek Angkek. In this method, data is also collected through sources related to personal models from various literature such as Google Books, journals, repositories and various other literature that supports the discussion of this article. The results of the research show 1). Teachers still use conventional models so that students feel bored when learning takes place 2). The Role Playing model has been implemented well, which focuses more on social interaction and student cohesion 3). The role playing model makes students active in speaking and enthusiastic about learning.